Policing distracted driving: contemporary challenges in roads policing - Savigar-Shaw, Leanne (Palgrave's critical policing studies, 2023)
This book draws on original research and existing theoretical perspectives and frameworks to critically examine the role of roads policing and its place within the wider field of policing. It looks at the challenges and complexities of doing roads policing and experiencing roads policing from the perspectives of police officers and the public. It uses distracted driving, and more specifically mobile phone use, as an evidence-based case study for a common issue to examine the contribution it makes to collisions, and the challenges of policing it as a driver behaviour. It also discusses broader issues such as the role of roads policing, police legitimacy, the interpretation of law, the interpretation of risk and generating compliance with the law. It speaks to both policing scholars and practitioners, as well as policy makers and road safety organisations